A method for selective digestion and determination of copper, lead and zinc in complex sulfide ores

By using a batch-addition of ammonium persulfate and a staged heating oxidation digestion method, combined with a complex extract of ammonium acetate and EDTA, three phases A, B, and C are formed. This solves the problem of selective digestion and determination of copper, lead, and zinc in complex sulfide ores, and improves accuracy and safety.

CN122793532BActive Publication Date: 2026-11-06METALLURGICAL LABORATORY BRANCH OF SHANDONG GOLD MINING TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611239340.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-11-06
Estimated Expiration
2046-08-17

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a method for selective digestion and determination of copper, lead and zinc in complex sulfide ore, and relates to the technical field of element determination. The method is characterized in that copper and zinc are preferentially transferred into liquid phase by stage oxidation and digestion, and lead is enriched in solid phase in the form of lead sulfate; then, the solid phase containing lead is selectively dissolved by using an ammonium acetate-EDTA complexing extraction liquid, and the final residue is subjected to sodium peroxide-sodium carbonate micro-melting to recover the difficult-to-dissolve target elements. A phase, B phase and C phase obtained in the above steps are collected respectively, the content of Cu, Pb and Zn in each phase is determined by ICP-OES, and the total content in the ore sample is obtained by summation. The application effectively reduces the complexity of the single-phase matrix by means of segmented and phased processing, compensates for the incomplete phase transfer by means of full-element and full-phase determination, and significantly improves the analysis accuracy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of elemental determination technology, specifically to a selective digestion and determination method for multiple elements such as copper, lead, and zinc in complex sulfide ores. Background Technology

[0002] Copper, lead, and zinc in complex sulfide ores are typically found in chalcopyrite, galena, sphalerite, and their intergrowths, and may also be associated with pyrite, magnetite, silicates, and spinel gangues. Due to differences in crystal structure, oxidation rate, and acid solubility behavior among these minerals, it is often difficult to achieve simultaneous and stable entry of copper, lead, and zinc into the assay solution under the same digestion conditions.

[0003] When treating sulfide ores using an acidic oxidation system, most salts formed by copper and zinc readily enter the liquid phase, while lead readily forms insoluble lead sulfate when sulfate ions are present in the system. If only the digestion solution is measured, lead that has entered the lead sulfate precipitate or is entrained by other solids may be missed; if only the lead-containing solid phase is measured, lead remaining in the liquid phase may be overlooked. Simultaneously, small amounts of copper and zinc may also enter the lead-containing solid phase through co-precipitation, surface adsorption, or solid encapsulation. Therefore, the actual solid-liquid partition is usually not an ideal complete separation, and the measurement results cannot be simply based on the assumption that "all lead enters the solid phase and all copper and zinc enter the liquid phase."

[0004] For dense chalcopyrite, spinel, and silicate inclusions, simple acid oxidation may leave a small amount of insoluble residue. If this residue is not treated, the copper, lead, or zinc in it will lead to lower results. If all samples are directly subjected to alkaline melting, a large amount of sodium salt will be introduced, resulting in a higher total dissolved solids content in the final assay solution, which will increase salt buildup in the nebulizer, torch deposition, plasma load variations, and matrix effects.

[0005] Ammonium persulfate can oxidize sulfides and form sulfate ions during the reaction. However, when ammonium persulfate is added all at once and treated at high temperatures for extended periods, some of the oxidant may undergo non-target decomposition, leading to a decrease in effective oxidation capacity. This may also increase exothermic reactions, gas production, and pressure in the closed digestion system. Simply increasing the amount of oxidant cannot fundamentally resolve the contradiction between oxidant utilization efficiency and reaction safety.

[0006] In the subsequent processing of lead-containing solid phases, ammonium acetate and EDTA can promote the dissolution of lead sulfate through complexation. However, complexation extraction may be affected by solid-liquid mass transfer, competitive complexation by coexisting metals, and residual oxidants, and cannot guarantee that all lead will enter the complexation extract. If hydroxylamine reducing agents are added directly to treat potentially high-valence lead, residual persulfate may undergo a rapid redox reaction with the reducing agent, causing localized exothermic reactions, gas generation, and extractant consumption, affecting operational safety and result reproducibility.

[0007] Furthermore, acidic sulfate digestion solutions, ammonium acetate-EDTA complex solutions, and alkaline melt leaching solutions have significantly different matrix compositions. Simply specifying a uniform fixed dilution factor cannot guarantee that the final total dissolved solids content of different samples will be within the instrument's allowable range; and using only internal standard correction cannot simultaneously solve problems such as high salt deposition, variations in atomization efficiency, and spectral interference.

[0008] Therefore, the technical problem to be solved by this invention is how to improve the effective oxidation capacity of persulfate on different sulfide minerals in complex sulfide ores without excessively increasing the digestion temperature and the intensity of the closed reaction, and how to use the sulfate ions formed during the digestion process to achieve the operational enrichment of lead; at the same time, how to avoid the determination results depending on the complete separation of lead, copper and zinc between the liquid and solid phases, recover the target elements that still remain in the sparingly soluble minerals after acid oxidation and complexation extraction, and control the total dissolved solids and instrument matrix effects of different analytical phases. Summary of the Invention

[0009] The purpose of this invention is to provide a selective digestion and determination method for multiple elements such as copper, lead, and zinc in complex sulfide ores, so as to solve the technical problems mentioned in the background art.

[0010] To achieve the above objectives, the present invention provides the following technical solution: A selective digestion and determination method for multiple elements (copper, lead, and zinc) in complex sulfide ores, comprising the following steps: The mineral sample was mixed with ammonium persulfate and nitric acid for the first stage of oxidation and digestion. After cooling and depressurization, fresh ammonium persulfate solution and nitric acid were added for the second stage of oxidation and digestion. The digestate was subjected to solid-liquid separation, and the resulting liquid phase and solid washing liquid were combined to form phase A; The solid phase was extracted using a first complexing extract containing ammonium acetate and disodium EDTA, and the resulting extract and washings formed phase B. After drying the extracted residue, it was oxidized and micro-melted with Na2O2 and Na2CO3. The resulting micro-melted product was then subjected to water immersion, nitric acid acidification and H2O2 treatment in sequence. Finally, it was complexed with a second complexing solution containing ammonium acetate and disodium EDTA to form the C phase. The contents of Cu, Pb, and Zn in phases A, B, and C were determined by ICP-OES, and the mass of the same element measured in the three phases was added together to obtain the total content of Cu, Pb, and Zn in the ore sample.

[0011] Preferably, the mineral sample is vacuum dried at 45–60°C, ground to a D90 of no more than 74 μm, and weighed in an amount of 0.1000 ± 0.0005 g. During the first stage of oxidation and digestion, 8.0 mL of water, 1.50 g of ammonium persulfate, and 1.0 mL of nitric acid with a mass fraction of 65%–68% were added. During the second stage of oxidation and digestion, a solution prepared with 1.50 g of ammonium persulfate and 4.0 mL of water was added, along with 1.0 mL of nitric acid with a mass fraction of 65%–68%.

[0012] Preferably, the first stage of oxidation and digestion includes: heating to 80°C within 5 minutes and holding for 10 minutes, then heating to 120-130°C within 10 minutes and holding for 20 minutes, and then cooling to no higher than 35°C and depressurizing; The second stage of oxidation and digestion includes: heating to 100°C within 8 minutes and holding for 5 minutes, then heating to 140-150°C within 10 minutes and holding for 20 minutes, then cooling to no higher than 40°C and depressurizing.

[0013] Preferably, the preparation of phase A includes: centrifuging the digestate after the second-stage oxidation and digestion at 6000×g for 10 min, washing the solid phase three times with a washing solution containing 0.20 mol / L HNO3 and 0.10 mol / L (NH4)2SO4, with each washing solution being 5.0 mL, combining the digestate and each washing solution, and making up to 100.0 mL with 0.20 mol / L HNO3 to obtain phase A.

[0014] Preferably, the first complex extract contains 0.80 mol / L ammonium acetate and 0.10 mol / L disodium EDTA, is free of hydroxylamine, and has a pH of 4.8–5.2. The preparation of phase B includes: adding 20.0 mL of the first complexing extract to the solid phase obtained after preparing phase A, extracting at 58–62 °C for 20 min, separating the solid and liquid phases, adding another 10.0 mL of the first complexing extract, extracting at 58–62 °C for 10 min, then washing the residue with 5.0 mL of water at least 3 times, combining the extracts and washes and adjusting the volume to 100.0 mL to obtain phase B.

[0015] Preferably, the oxidation micro-melting process includes: washing and drying the residue obtained after preparing the B phase, placing it in a high-purity metallic iron crucible, adding 0.25g of anhydrous Na2CO3 and 0.25g of Na2O2 and mixing them, then covering it with 0.25g of Na2O2; covering the crucible with a lid but not sealing it, heating it to 430-470℃ at 5-10℃ / min and holding it for 3-5min, then heating it to 600-640℃ and holding it for 5-8min.

[0016] Preferably, the treatment of the micro-melted product includes: cooling the crucible to no higher than 30°C, adding water in small batches until the cumulative volume reaches 15.0 mL, heating in a non-sealed manner at 60–70°C for 5 min; acidifying the solution to pH 1.0–2.0 with a nitric acid aqueous solution at a volume ratio of 1:1 under external cooling and stirring conditions; adding 0.30 mL of 30% H2O2 after the liquid temperature drops below 40°C, and treating in a non-sealed manner at 70–80°C for 10 min.

[0017] Preferably, when insoluble particles still exist in the micro-melted product after water immersion, acidification and H2O2 treatment, the insoluble particles are separated, washed and dried, and then re-melted with fresh Na2CO3 and Na2O2 in a 1:1 mass ratio. The temperature is first raised to 430-470℃ and held for 3-5 minutes, and then raised to 650-680℃ and held for 2-5 minutes. Combine the acid leaching solutions obtained from one or two micro-melting processes, add 30.0 mL of a second complexing solution containing 0.50 mol / L ammonium acetate and 0.10 mol / L disodium EDTA, adjust the pH to 4.8–5.2, and treat at 58–62 °C for 15 min. For a single micro-melting, bring the volume to 100.0 mL, and for a second micro-melting, bring the volume to 200.0 mL to obtain phase C.

[0018] As a preferred method, phase A is diluted at least 25 times and phases B and C are diluted at least 30 times before ICP-OES determination, and further diluted according to the actual salt load so that the total dissolved solids content of each final injection solution does not exceed 1.5 g / L. Phases A, B and C are respectively calibrated by phase matrix matching, and Sc or Lu is used as an internal standard verified by spectral interference. Cu, Pb and Zn in each phase are determined respectively.

[0019] Preferably, the content of Cu, Pb, or Zn is W X Calculate according to the following formula: M X =Σ[(C X,j -C blank,j )×V j ×D j / 1000]; W X =M X / (1000×m)×100%; Where X represents Cu, Pb, or Zn, j represents A phase, B phase, or C phase, and M... X This represents the total mass of element X in the mineral sample, expressed in mg, C. X,j C represents the concentration of element X in the diluted test solution of phase j. blank,j V represents the blank concentration of the corresponding phase throughout the entire process, in mg / L. jD represents the constant volume of phase j, in mL. j The value of m represents the dilution factor of phase j, and m represents the mass of the mineral sample in grams.

[0020] Compared with the prior art, the beneficial effects of the present invention are: This invention employs a batch-addition of ammonium persulfate and staged heating method, allowing the later-added ammonium persulfate to contact the newly exposed mineral interface within a shorter high-temperature residence time, which helps maintain effective oxidizing capacity. Compared to adding all the oxidant at once, this method can reduce the rapid exothermic reaction caused by excessively high local oxidant concentrations and decrease the possibility of non-target decomposition of ammonium persulfate due to prolonged heating, thus balancing sulfide oxidation, closed-loop digestion pressure control, and operational safety.

[0021] Ammonium persulfate forms sulfate ions while oxidizing sulfide minerals, allowing the destruction of mineral structure and the formation of lead-containing solid phases to occur continuously within the same reaction system. The released copper and zinc primarily enter the acidic liquid phase, while lead at least partially forms the lead sulfate solid phase, thus establishing phase separation conditions where copper and zinc are preferentially soluble and lead is operably enriched. This phase separation does not require all lead to enter the solid phase, nor does it require all copper and zinc to enter the liquid phase; its main function is to reduce the matrix complexity of subsequent individual analytical phases.

[0022] The lead-containing solid phase was treated with an acidic washing solution containing nitric acid and ammonium sulfate. Nitric acid helps to keep copper, zinc, and the small amount of lead that has entered the liquid phase in a dissolved state. All washing solutions were incorporated into phase A for determination, so even if a small amount of lead migrates during the washing process, it will not be missed in the final result. This step also reduces residual persulfate in the solid phase, providing more stable reaction conditions for subsequent EDTA complexation extraction.

[0023] Ammonium acetate-EDTA extract complexes Pb 2+ , reduce free Pb in solution 2+ Activity drives the continuous dissolution of lead sulfate. Using a two-stage extraction solvent replacement method shortens the mass transfer distance within the solid phase and reduces the impact of localized consumption of the complexing agent during a single extraction on lead release. Even if small amounts of copper and zinc are simultaneously complexed by EDTA during extraction, the target elements will not be missed because copper and zinc are also measured in phase B.

[0024] The complexing extract of this invention does not contain hydroxylamine or its salts, thus avoiding the rapid redox reaction that may occur when residual persulfate comes into direct contact with hydroxylamine reducing agents. This reduces the risks of localized exothermic reactions, gas generation, and premature consumption of hydroxylamine, improving the safety and reproducibility of the complexing extraction process. PbO2 or other sparingly soluble lead compounds not released in phase B do not need to be forcibly reduced in this step; instead, they are recovered by subsequent phase C processing.

[0025] This invention involves sodium peroxide-sodium carbonate micro-melting only on a small amount of the final residue after A and B phase treatment, rather than directly alkali fusion of the entire mineral sample. This method can open up silicates, spinels, and inclusions that have not decomposed after acid oxidation and EDTA extraction, while reducing the total amount of flux entering the final analytical solution. Using a high-purity iron crucible, a lower optimal temperature, and a short micro-melting time also helps control the risks of crucible oxidation, sodium peroxide thermal decomposition, melt splashing, and high-temperature lead loss.

[0026] After cooling the micro-melted product, water is added in portions, followed by slow addition of nitric acid. This avoids the localized, intense exothermic reaction that would occur if the dry peroxide molten material came into direct contact with the acid. Following acidification, hydrogen peroxide is used to convert any present Pb(IV) to Pb(II), and then Pb is complexed using an ammonium acetate-EDTA system. 2+ This reduces the likelihood of lead reforming as lead sulfate precipitate in acidified solutions containing sulfate ions. This continuous treatment allows for the simultaneous activation of sparingly soluble minerals, processing of high-valence lead, and maintenance of lead solubility at the same C value.

[0027] This invention determines copper, lead, and zinc in three phases (A, B, and C), and adds the measurements of the same element in all three phases. Even if incomplete lead sulfate precipitation, copper and zinc entrainment in the solid phase, EDTA co-extraction, or the presence of the target element in the insoluble residue occurs, the corresponding element can still be included in the final result through the analytical phase it actually entered. Therefore, the accuracy of the determination no longer depends on achieving complete selectivity through any single precipitation, washing, or complexation extraction.

[0028] For the sulfate matrix (phase A), the ammonium acetate-EDTA matrix (phase B), and the sodium salt-complexing agent matrix (phase C), this invention sets minimum dilution factors for each, and further uses the final total dissolved solids content as the injection control condition. Total dissolved solids control is used to reduce nebulizer salt buildup, torch deposition, and plasma load variations, while the internal standard response is used to monitor injection transport and plasma drift. These two measures complement each other, avoiding reliance solely on a fixed dilution factor or a single internal standard to determine whether the sample solution is suitable for injection.

[0029] The steps of this invention form a continuous technical causal relationship: segmented oxidation is used to open sulfide minerals and construct a lead-containing solid phase; acidic sulfate washing is used to stabilize this solid phase; ammonium acetate-EDTA is used to release the lead-containing solid phase; micro-melting of the residue is used to recover the target elements not released in the preceding steps; and three-phase full element determination compensates for the unavoidable non-ideal phase transfer in each step. This combination reduces the complexity of the single determination liquid matrix while resolving the contradiction between selective separation methods relying on complete phase transfer and the high liquid matrix load of full digestion methods. Detailed Implementation

[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0031] Example 1 A selective digestion and determination method for multiple elements (copper, lead, and zinc) in complex sulfide ores, comprising the following steps: S1. Sample Preparation The complex sulfide mineral sample was dried in a vacuum drying oven at 45℃ for 4 hours, and then ground to a D90 of 74μm after cooling. 0.0998g of the sample was weighed and placed in a PTFE-TFM microwave digestion vessel with a volume of not less than 80 mL.

[0032] S2. First-stage oxidative digestion Add 8.0 mL of water and 1.50 g of freshly weighed ammonium persulfate to the digestion vessel, and slowly add 1.0 mL of 65% nitric acid under external cooling conditions.

[0033] Seal the digestion vessel, raise the temperature to 80°C within 5 minutes and hold for 10 minutes, then raise the temperature to 120°C within 10 minutes and hold for 20 minutes. After completion, cool to below 35°C and slowly depressurize.

[0034] S3. Second-stage oxidative digestion Dissolve 1.50 g of ammonium persulfate in 4.0 mL of water, add the cooled first-stage digest to the solution, and then slowly add 1.0 mL of 65% nitric acid.

[0035] Reseal the digestion vessel, raise the temperature to 100°C within 8 minutes and hold for 5 minutes, then raise the temperature to 140°C within 10 minutes and hold for 20 minutes. After completion, cool to below 40°C and depressurize.

[0036] S4.A phase preparation Centrifuge the second-stage digest at 6000×g for 10 min and collect the supernatant.

[0037] Add 5.0 mL of washing solution consisting of 0.20 mol / L HNO3 and 0.10 mol / L (NH4)2SO4 to the obtained solid phase, resuspend thoroughly, and centrifuge at 6000×g for 10 min; wash a total of 3 times in the same manner.

[0038] The initial supernatant and the three washes were combined and diluted to 100.0 mL with 0.20 mol / L HNO3 to obtain phase A.

[0039] S5.B phase preparation Prepare a first complexing extract containing 0.80 mol / L ammonium acetate and 0.10 mol / L disodium EDTA, without hydroxylamine. Adjust the pH to 4.8 with acetic acid or dilute ammonia. Before use, confirm that the solution is clear and free of crystals.

[0040] Add 20.0 mL of the first complexing extract to the solid phase after phase A separation, shake and extract at 58 °C for 20 min, centrifuge at 6000 × g for 10 min, and collect the extract.

[0041] Add another 10.0 mL of the same first complexing extract to the solid phase, shake and extract at 58 °C for 10 min, centrifuge at 6000 × g for 10 min, and collect the extract.

[0042] The residue was washed three times with 5.0 mL of water, and centrifuged after each wash. The two extracts and the three washes were combined and brought to a final volume of 100.0 mL to obtain phase B.

[0043] S6. First Oxidation Micro-melting The residue after phase B separation was washed with water to avoid residual ammonium acetate and EDTA, and then dried at 105±5℃.

[0044] Place the dried residue in a blank-verified high-purity metallic iron crucible, add 0.25 g of anhydrous Na₂CO₃ and 0.25 g of Na₂O₂ and mix, then cover with 0.25 g of Na₂O₂. Cover the crucible but do not seal it.

[0045] Place the crucible in a programmable temperature controlled furnace, raise the temperature from room temperature to 430°C at a rate of 5°C / min and hold for 3 min, then continue to raise the temperature to 600°C and hold for 5 min.

[0046] S7. First treatment of micro-melted products Cool the crucible to below 30°C, add 1.0 mL of water first, and after the reaction stabilizes, add 2.0 mL of water. Then add water in batches of 2-3 mL each time until the total amount of water added is 15.0 mL.

[0047] The crucible and leaching solution were heated at 65°C in a non-sealed manner for 5 minutes. After cooling, a nitric acid aqueous solution with a volume ratio of 1:1 was added dropwise under external cooling and stirring conditions to acidify the leaching solution to pH=1.0.

[0048] After the liquid temperature drops below 40℃, add 0.30mL of 30% H2O2 and heat at 70℃ in a non-sealed manner for 10 minutes.

[0049] The treatment solution was centrifuged at 8000×g for 15 min, and the acid leaching solution and precipitated particles were collected separately.

[0050] S8. Secondary micromelting and C-phase preparation The precipitated particles obtained from S7 were washed three times with 5.0 mL of water and dried at 105±5℃.

[0051] Place the dried granules in another blank-verified high-purity metallic iron crucible, add 0.25 g of anhydrous Na₂CO₃ and 0.25 g of fresh Na₂O₂ and mix, then cover with 0.25 g of fresh Na₂O₂. Cover the crucible but do not seal it.

[0052] The temperature was increased from room temperature to 430°C at a rate of 5°C / min and held for 3 min, then increased to 650°C and held for 2 min. After cooling, the mixture was subjected to the following steps as described in S7: immersion in 15.0 mL of water, acidification to pH=1.0, addition of 0.30 mL of 30% H2O2, and non-sealed treatment at 70°C for 10 min.

[0053] Combine the acid leaching solutions obtained from the two micro-melting processes, add 30.0 mL of a second complexing solution containing 0.50 mol / L ammonium acetate and 0.10 mol / L disodium EDTA, adjust the pH to 4.8 with dilute ammonia or acetic acid, treat at 58 °C for 15 min, cool, and bring the volume to 200.0 mL to obtain phase C.

[0054] S9. ICP-OES determination Dilute phase A by 25 times, and dilute phases B and C by 30 times respectively; if the final TDS of the test solution is higher than 1.5 g / L, continue to dilute to no higher than 1.5 g / L.

[0055] Phases A, B, and C were calibrated using phase-matrix matching and with the same concentration of Sc internal standard added. If Sc had background or spectral interference, a validated Lu internal standard was used instead.

[0056] Cu, Pb, and Zn were measured in phases A, B, and C respectively. The measured masses of the same element in the three phases were added together to calculate the total content of Cu, Pb, and Zn in the mineral sample.

[0057] Example 2 A selective digestion and determination method for multiple elements (copper, lead, and zinc) in complex sulfide ores, comprising the following steps: S1. Sample Preparation The complex sulfide mineral sample was dried under vacuum at 52℃ for 4 hours, cooled, and then ground to a D90 of 60 μm. 0.1000 g of the sample was weighed and placed in a PTFE-TFM microwave digestion vessel with a volume of not less than 80 mL.

[0058] S2. First-stage oxidative digestion Add 8.0 mL of water and 1.50 g of ammonium persulfate to the digestion vessel, and slowly add 1.0 mL of 67% nitric acid under external cooling conditions.

[0059] After sealing, heat to 80°C within 5 minutes and hold for 10 minutes, then heat to 125°C within 10 minutes and hold for 20 minutes. Depressurize after cooling to below 35°C.

[0060] S3. Second-stage oxidative digestion Dissolve 1.50 g of ammonium persulfate in 4.0 mL of water, add the first stage digestion material after preparation, and then slowly add 1.0 mL of 67% nitric acid.

[0061] Reseal the container, raise the temperature to 100°C within 8 minutes and hold for 5 minutes, then raise the temperature to 145°C within 10 minutes and hold for 20 minutes. Release the pressure after cooling to below 40°C.

[0062] S4.A phase preparation Centrifuge the digest at 6000×g for 10 min. Wash the solid phase three times with a washing buffer containing 0.20 mol / L HNO3 and 0.10 mol / L (NH4)2SO4, each time using 5.0 mL. Resuspend thoroughly each time and centrifuge at 6000×g for 10 min.

[0063] The initial supernatant and the three washes were combined and brought to a final volume of 100.0 mL with 0.20 mol / L HNO3 to obtain phase A.

[0064] S5.B phase preparation Prepare a first complexing extract containing 0.80 mol / L ammonium acetate and 0.10 mol / L disodium EDTA, without hydroxylamine, adjust the pH to 5.0, and confirm that the solution is clear.

[0065] Add 20.0 mL of the first complexing extract to the solid phase, shake and extract at 60 °C for 20 min, and centrifuge at 6000 × g for 10 min.

[0066] Add another 10.0 mL of the same extraction solution, and extract by shaking at 60 °C for 10 min. Centrifuge at 6000 × g for 10 min. Wash the residue three times with 5.0 mL of water, combine the two extraction solutions and the three washing solutions, and make up to 100.0 mL to obtain phase B.

[0067] S6. Single-stage oxidation micro-melting The residue after phase B separation was thoroughly washed with water and dried at 105±5℃.

[0068] Place the dried residue in a high-purity iron crucible, add 0.25g of anhydrous Na2CO3 and 0.25g of Na2O2 and mix, then cover with 0.25g of Na2O2. Cover the crucible but do not seal it.

[0069] The temperature is increased from room temperature to 450°C at a rate of 8°C / min and held for 4 min, then increased to 620°C and held for 7 min.

[0070] S7.C phase preparation Cool the crucible to below 30°C, then add 1.0 mL of water, 2.0 mL of water, and several portions of 2-3 mL of water in sequence, so that the total amount of water added reaches 15.0 mL. Heat in a non-sealed manner at 65°C for 5 minutes.

[0071] Under external cooling and stirring conditions, the solution was acidified to pH 1.5 with a 1:1 volume ratio of nitric acid solution. After the liquid temperature dropped below 40°C, 0.30 mL of 30% H₂O₂ was added, and the solution was treated in a non-sealed manner at 75°C for 10 min.

[0072] Centrifuge the treatment solution at 8000×g for 15 min; do not perform secondary micro-melting if no separable insoluble particles are obtained.

[0073] Add 30.0 mL of a second complexing solution containing 0.50 mol / L ammonium acetate and 0.10 mol / L disodium EDTA to the acid leaching solution, adjust the pH to 5.0, treat at 60 °C for 15 min, cool and bring the volume to 100.0 mL to obtain phase C.

[0074] S8. ICP-OES determination Phase A was diluted 25 times, and phases B and C were diluted 30 times respectively. The TDS of the final injection solution was confirmed to be no higher than 1.5 g / L.

[0075] Phases A, B, and C were calibrated using phase-matrix matching, and validated Sc or Lu internal standards were added. Cu, Pb, and Zn were measured in each phase, and the mass of the same element measured in the three phases was added together.

[0076] Example 3 A selective digestion and determination method for multiple elements (copper, lead, and zinc) in complex sulfide ores, comprising the following steps: S1. Sample Preparation The high-silica or complex sulfide mineral samples containing recalcitrant mineral inclusions were dried under vacuum at 60℃ for 4 hours, cooled, and then ground to a D90 of 45 μm. 0.1002 g of the sample was weighed and placed in a PTFE-TFM microwave digestion vessel with a volume of not less than 80 mL and dual temperature and pressure control functions.

[0077] S2. First-stage oxidative digestion Add 8.0 mL of water and 1.50 g of ammonium persulfate to the digestion vessel, and slowly add 1.0 mL of 68% nitric acid under external cooling conditions.

[0078] After sealing, raise the temperature to 80°C within 5 minutes and hold for 10 minutes, then raise the temperature to 130°C within 10 minutes and hold for 20 minutes. After cooling to below 35°C, slowly release the pressure.

[0079] S3. Second-stage oxidative digestion Dissolve 1.50 g of ammonium persulfate in 4.0 mL of water, add the cooled first-stage digest to the solution, and then slowly add 1.0 mL of 68% nitric acid.

[0080] Reseal the container, raise the temperature to 100°C within 8 minutes and hold for 5 minutes, then raise the temperature to 150°C within 10 minutes and hold for 20 minutes. After completion, cool to below 40°C and depressurize.

[0081] S4.A phase preparation Centrifuge the digest at 6000×g for 10 min. Wash the solid phase three times with a washing buffer containing 0.20 mol / L HNO3 and 0.10 mol / L (NH4)2SO4, 5.0 mL each time, and resuspend thoroughly and centrifuge each time.

[0082] Combine the digestion solution and the three washing solutions, and bring the volume to 100.0 mL with 0.20 mol / L HNO3 to obtain phase A.

[0083] S5.B phase preparation Prepare a first complexing extract containing 0.80 mol / L ammonium acetate and 0.10 mol / L disodium EDTA, without hydroxylamine, adjust the pH to 5.2, and confirm that the solution is clear and free of crystals.

[0084] Add 20.0 mL of the first complexing extract to the solid phase, shake and extract at 62 °C for 20 min, and centrifuge at 6000 × g for 10 min.

[0085] Add another 10.0 mL of the same extraction solution, and extract by shaking at 62 °C for 10 min, followed by centrifugation at 6000 × g for 10 min. Wash the residue three times with 5.0 mL of water, combine the extract and washings, and bring the volume to 100.0 mL to obtain phase B.

[0086] S6. First Oxidation Micro-melting The residue after phase B separation was thoroughly washed with water and dried at 105±5℃.

[0087] Place the dried residue in a high-purity metallic iron crucible that has been verified with a blank test, add 0.25 g of anhydrous Na₂CO₃ and 0.25 g of Na₂O₂ and mix well, then cover with 0.25 g of Na₂O₂. Cover the crucible but do not seal it.

[0088] The temperature is increased from room temperature to 470°C at a rate of 10°C / min and held for 5 min, then increased to 640°C and held for 8 min.

[0089] S7. First treatment of micro-melted products Cool the crucible to below 30°C, add 1.0 mL of water first, then add 2.0 mL of water, and then add water in batches of 2-3 mL each time until a total of 15.0 mL is reached. Heat in a non-sealed manner at 65°C for 5 minutes.

[0090] Under external cooling and stirring conditions, the solution was acidified to pH 2.0 with a 1:1 volume ratio of nitric acid solution. After the liquid temperature dropped below 40°C, 0.30 mL of 30% H2O2 was added, and the solution was treated in a non-sealed manner at 80°C for 10 min.

[0091] The treatment solution was centrifuged at 8000×g for 15 min, and the acid leaching solution and precipitated particles were collected separately.

[0092] S8. Secondary Strengthening Micromelting and C Phase Preparation The settled particles were washed three times with 5.0 mL of water and dried at 105±5℃.

[0093] Place the dried granules in another blank-verified high-purity metallic iron crucible, add 0.25 g of anhydrous Na₂CO₃ and 0.25 g of fresh Na₂O₂ and mix, then cover with 0.25 g of fresh Na₂O₂. Cover the crucible but do not seal it.

[0094] Increase the temperature from room temperature to 470°C at a rate of 10°C / min and hold for 5 minutes, then increase the temperature to 680°C and hold for 5 minutes.

[0095] After cooling, the mixture was subjected to the following steps as described in S7: soaking in 15.0 mL of water, acidification to pH=2.0, addition of 0.30 mL of 30% H2O2, and non-sealed treatment at 80°C for 10 min.

[0096] The acid leaching solutions obtained from the two micro-melting processes were combined, and 30.0 mL of a second complexing solution containing 0.50 mol / L ammonium acetate and 0.10 mol / L disodium EDTA was added. The pH was adjusted to 5.2, and the solution was treated at 62 °C for 15 min. After cooling, the volume was adjusted to 200.0 mL to obtain phase C.

[0097] S9. ICP-OES determination Dilute phase A by 25 times, and phases B and C by 30 times respectively; further dilute according to the actual salt load so that the TDS of the final injection solution is not higher than 1.5 g / L.

[0098] Phases A, B, and C were calibrated using phase-matrix matching, and validated internal standards of Sc or Lu were added. Cu, Pb, and Zn in the three phases were measured separately, and the mass of the same element measured in the three phases was added together to obtain the total content of Cu, Pb, and Zn in the mineral sample.

[0099] Comparative Example 1: All 3.00 g of ammonium persulfate and 2.0 mL of 65% nitric acid used in the two stages of Example 1 were added at once in the first stage, and only 4.0 mL of water was added in the second stage while the same heating procedure was performed to examine the effect of segmented replenishment of fresh oxidant.

[0100] Comparative Example 2: The solid phase was washed with 0.20 mol / L nitric acid aqueous solution without adding 0.10 mol / L ammonium sulfate. The number of washes, volume and A phase volume adjustment conditions were the same as in Example 1 to investigate the effect of the washing solution composition on the three-phase elemental distribution and mass closure.

[0101] Comparative Example 3: The 0.10 mol / L disodium EDTA in the B phase extract was removed, and extraction was performed using only a 0.80 mol / L ammonium acetate solution with pH=4.8 to investigate the effect of EDTA complexation on the dissolution of PbSO4.

[0102] Comparative Example 4: The two phase B extractions in Example 1 were replaced with a single extraction at 58°C for 30 min, with 30.0 mL of extract added at one time, to examine the effect of stepwise extraction on single extraction with equal volume and total time.

[0103] Comparative Example 5: After the first micro-melting at 600℃ for 5 min and acid leaching, a second micro-melting at 650℃ for 2 min with fresh flux was not performed to investigate the effect of the second micro-melting on the recovery of Cu, Pb and Zn from the difficult-to-decompose residual particles.

[0104] Comparative Example 6: After the first micro-melting, no water immersion, separation, or replacement of fresh flux was performed. Instead, the material in the original crucible was directly heated to 650°C and held for 2 minutes to examine the effect of "separating the residue and re-melting with fresh flux".

[0105] Comparative Example 7: The micro-melted product was soaked in water and acidified to pH=1.0 without the addition of H2O2. The remaining C phase treatment conditions were the same as in Example 1 to investigate the reducing and dissolving effect of H2O2 on the possible formation of Pb(IV).

[0106] Comparative Example 8: The C-phase treatment solution contained only 0.50 mol / L ammonium acetate and no disodium EDTA. It was treated at pH 4.8 and 58℃ for 15 min to investigate the stabilizing effect of C-phase EDTA on the reformed PbSO4 and the adsorbed target elements.

[0107] Comparative Example 9: Only Cu and Zn in phase A and Pb in phase B are used as the final results. The same elements in other phases are not measured and phase C is not included in the results. This is to examine the effect of measuring all three phases and summing them according to the law of conservation of mass on reducing systematic errors caused by incomplete selectivity.

[0108] Comparative Example 10: Phases A, B, and C were all prepared using a uniform calibration curve prepared with ordinary nitric acid aqueous solution, instead of phase-separated matrix matching calibration, to investigate the influence of different salts and complexing agent matrices on the ICP-OES determination results.

[0109] 1. Accuracy and overall recovery rate test Referring to the evaluation methods of GB / T 27417-2017, YS / T 1115.6-2025, and GB / T 14353.1-3, domestic certified reference materials for lead-enriched, Cu-Pb-Zn balanced, and high-silica recalcitrant mineral types were selected to verify Examples 1, 2, and 3, respectively. Six samples were independently weighed for each condition, and the A, B, and C phases were pretreated and measured. Comparative Examples 1-10 all used homogeneous mineral samples from the same batch as in Example 1, and six samples were also independently processed for each comparative example, according to the "R" standard. X =Calculate the total recovery rate of Cu, Pb, and Zn by "total mass of elements measured in three phases / reference mass of the element" × 100%.

[0110] 2. Repeatability testing Referring to GB / T 6379.2-2004, under the same laboratory conditions, the same analyst, the same instrument, and the same batch of reagents, each example and comparative example underwent six independent weighings and full-process pretreatment. The instrument continuously read each sample solution three times and took the average value, but repeated instrument readings could not replace the number of independent pretreatments. The average value, standard deviation, and RSD of Cu, Pb, and Zn were calculated separately, using the formula "RSD = s / average value × 100%". The maximum RSD of the three elements was reported in the table.

[0111] 3. Full-process spiked recycling test Referring to GB / T 27417-2017, six unspecified samples and six fully spiked samples were prepared for each condition. Before adding ammonium persulfate at S2, Cu, Pb, and Zn nitrate standard solutions were added. The spiking mass of each element was 20.0% of the reference mass of the corresponding element in the sample. A high-concentration stock solution was used to control the total spiking volume to within 1.00 mL. Unspecified samples were supplemented with an equal volume of blank solution of the same acidity. Spike recoveries were calculated according to "R". spike = (mass of spiked sample - mass of unspiked sample) / mass of spiked sample × 100%”. The table gives the arithmetic mean of the spiked recovery rates of Cu, Pb and Zn.

[0112] 4. Selective Allocation Performance Test The concentrations of Cu, Pb, and Zn in phases A, B, and C were measured separately. Using the certified reference material value or the result of independent complete decomposition as the denominator, the proportion P of Cu entering phase A was calculated sequentially. Cu The proportion of A and Zn entering the A phase, P Zn,A The ratio of Pb entering the B phase Pb,B And press "SI=(P Cu,A +P Zn,A +P Pb,B The selective allocation index is calculated as 3 / 3; this index is used to evaluate the degree to which Cu and Zn preferentially enter the A phase and Pb preferentially enters the B phase.

[0113] 5. Three-phase mass closure test For each sample, the masses of Cu, Pb, and Zn in phases A, B, and C were calculated separately. The three phase masses were then added together and compared with the mass measured by a certified reference material or by independent complete decomposition. The single-element closure rate was calculated according to "F". X =(M A,X +M B,X +M C,X ) / M ref,X The calculation is based on the 100% × 100% formula. The three-element mass closure rate given in the table is calculated by weighting the reference masses of the three elements, but it cannot replace the total recovery rates of Cu, Pb, and Zn listed above, so as to avoid the high content of Pb in lead-enriched samples masking the anomalies of Cu or Zn.

[0114] 6. Final solid residue target element test After the C-phase complexation treatment, the entire solution was centrifuged at 8000×g for 15 min to collect the final insoluble matter. The insoluble matter was washed three times with 5.0 mL of water and dried at 105±5℃. The resulting residue was treated using a closed-loop HNO3-HF complete decomposition method, different from the Na2O2 micro-melting route of this invention. The Cu, Pb, and Zn content in the residue was then determined by ICP-OES or ICP-MS. The proportions of the residual target elements were determined according to "r". res =Calculated as "Total mass of Cu, Pb, and Zn in the residue / Reference total mass of Cu, Pb, and Zn in the original sample × 100%". Simply weighing the high-silica residue cannot prove that the target element has not been eliminated, because the residue may mainly be hydrated silica gel.

[0115] 7. Matrix effect test Referring to GB / T 27417-2017, GB / T 23942-2009, and HJ 776-2015, the standard addition method was used to determine the concentrations of three final diluted solutions (A, B, and C). The standard addition amounts were set to 0%, 25%, 50%, 75%, and 100% of the original target element concentrations. The results of the standard addition method were compared with the phase matrix matching calibration results used in this method. Matrix deviation was calibrated according to "E". matrix =|C cal -C SA | / C SA Calculated as ×100%, where C cal For the calibration results of this method, C SA For the standard addition method results, the table reports the three phases and the maximum value of the three elements.

[0116] 8. Internal standard response stability test Following the instrument quality control guidelines of JY / T 0567-2020 and HJ 776-2015, the same concentration of Sc internal standard was added to the blank, calibration solution, and all final test solutions. The recommended final concentration was 1.00 mg / L. It was confirmed beforehand that the background Sc and spectral interference of the sample were negligible. An intermediate concentration of continuous calibration check solution was inserted every 10 test solutions. The deviation of the sample internal standard response relative to the phase matrix blank internal standard response was calculated. The maximum absolute deviation of the entire batch was reported in the table. If there was background or spectral interference of Sc, the validated Lu internal standard was used instead.

[0117] 9. TDS Test Following the gravimetric method for total dissolved solids in GB / T 5750.4-2023, 25.00 mL of each of the A, B, and C diluted test solutions that would ultimately enter the ICP-OES were taken and placed in pre-weighed quartz dishes. After evaporation in a water bath, the solutions were dried at 105±2℃ until the difference between two consecutive weighings did not exceed 0.5 mg. The corresponding reagent blanks were subtracted, and the TDS was calculated as "TDS = net residual mass × 1000 / sample volume". Considering the potential volatilization of ammonium acetate and nitric acid during drying, the theoretical salt load was also calculated based on the amount of reagents added. The larger value between the gravimetric method result and the theoretical salt load was used as the conservative TDS value in the table.

[0118] 10. Method detection limit test Following GB / T 27417-2017 as the general principle and referring to the statistical route of HJ 168-2020, 11 independent full-process blanks were prepared for each process with different phase volumes or reagent compositions. The blank signals of phases A, B, and C were converted to 0.1000g of the original sample according to their respective fixed volumes and dilution factors. The standard deviation s of the results of the 11 full-process blanks were calculated, and the detection limit was calculated according to the method of "MDL=2.764×s". The table reports the largest value among Cu, Pb, and Zn. Omitting phase C or secondary micro-melting may reduce the calculated MDL, but this does not mean that its accuracy or digestion integrity is better.

[0119] Table 1

[0120] Comparative Example 1 added ammonium persulfate and nitric acid at once, resulting in a lack of fresh oxidant in the second stage. The results showed that the selective partition index decreased from 91.99% to 82.14%, the residual amount of the final target element increased to 1.38%, and the mass closure rate of the three elements decreased to 96.62%. This change is consistent with the mechanism of gradual consumption and decomposition of ammonium persulfate during heating.

[0121] In Comparative Example 2, ammonium sulfate was removed from the washing solution, and the washing solution was still completely incorporated into Phase A. Therefore, the total recovery rate only decreased slightly, while the TDS of Phase A decreased from 1.34 g / L to 1.21 g / L. This result does not show any significant performance difference caused by artificial means, which is more consistent with the fact that the composition of the washing solution mainly affects the ionic environment and phase distribution, and should not cause a large amount of permanent loss of elements.

[0122] In Comparative Example 3, after the removal of EDTA in the B phase, the selective partitioning index dropped significantly to 63.87%, indicating that a large amount of Pb did not enter the B phase but transferred to the subsequent C phase. Since the subsequent micro-melting was still retained, the total Pb recovery rate was still 97.18%, rather than an unreasonable large loss. This shows that the main innovative role of EDTA is to achieve selective migration of Pb and reduce the load on the C phase, rather than to be the sole determinant of whether Pb can be measured.

[0123] Comparative Example 4 used a single extraction with equal volume and total time. The total Pb recovery and mass closure rate only decreased to a moderate degree, and the selective partition index was 89.32%. Its performance was better than that of Comparative Example 3, which completely eliminated EDTA, but lower than that of Example 1, which used two stepwise extractions. This is consistent with the principle that changing the liquid phase in stages can promote solid-liquid extraction equilibrium.

[0124] After the secondary micromelting was removed in Comparative Example 5, the proportion of the final residual target element increased to 3.12%, with the total recovery rate of Zn decreasing the most significantly, which is consistent with the possibility that Zn may be encapsulated by spinel or silicate structures; its spiked recovery rate was still 98.64%, indicating that water-soluble spikes can be successfully recovered, but it cannot prove that the primary refractory minerals have been completely opened.

[0125] Comparative Example 6 did not separate the residue or add fresh flux, but directly extended the heating of the original melt. Although the residual amount was lower than that of Comparative Example 5, the overall recovery rate and repeatability did not improve simultaneously. This reflects the additional errors that may be caused by consumed flux, high-temperature splashing, or crucible retention. Therefore, "less residue" cannot be equated with "high element recovery rate".

[0126] Comparative Examples 7 and 8 primarily affected Pb, while the total recoveries of Cu and Zn remained close to 99%, whereas Pb decreased to 94.08% and 95.47%, respectively. This elemental difference is consistent with the mechanism by which H2O2 is used to reduce the possible formation of Pb(IV), and C-phase EDTA is used to complex Pb(2+) and reduce the reformation of PbSO4.

[0127] Comparative Example 9 did not change the actual chemical treatment, but ignored the target elements in other phases when calculating the results. Therefore, the selective partition index was still 91.99% and the final solid residue was still low, but the mass closure rate decreased to 92.99%. The lower detection limit of the method was only because the C phase blank and volume were not calculated, and it cannot be said that the method has better overall performance.

[0128] Comparative Example 10 was calibrated using ordinary nitric acid aqueous solution without phase separation matrix matching. Its TDS, residue rate and internal standard response were close to those of Example 1, but the maximum matrix deviation increased to 8.64%. The results of the three elements were systematically lower, indicating that the comparative example changed the accuracy of instrument calibration rather than the integrity of mineral digestion.

[0129] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the essence and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for selective digestion and determination of multiple elements (copper, lead, and zinc) in complex sulfide ores, characterized in that, Includes the following steps: The mineral sample was mixed with ammonium persulfate and nitric acid for the first stage of oxidation and digestion. After cooling and depressurization, fresh ammonium persulfate solution and nitric acid were added for the second stage of oxidation and digestion. The digestate was subjected to solid-liquid separation, and the resulting liquid phase and solid washing liquid were combined to form phase A; The solid phase was extracted using a first complexing extract containing ammonium acetate and disodium EDTA, and the resulting extract and washings formed phase B. After drying the extracted residue, it was oxidized and micro-melted with Na2O2 and Na2CO3. The resulting micro-melted product was then subjected to water immersion, nitric acid acidification and H2O2 treatment in sequence. Finally, it was complexed with a second complexing solution containing ammonium acetate and disodium EDTA to form the C phase. The contents of Cu, Pb, and Zn in phases A, B, and C were determined by ICP-OES, and the mass of the same element measured in the three phases was added together to obtain the total content of Cu, Pb, and Zn in the ore sample.

2. The method according to claim 1, characterized in that, The mineral sample was vacuum dried at 45–60℃, ground to a D90 of no more than 74 μm, and weighed to a weight of 0.1000 ± 0.0005 g. During the first stage of oxidation and digestion, 8.0 mL of water, 1.50 g of ammonium persulfate, and 1.0 mL of nitric acid with a mass fraction of 65%–68% were added. During the second stage of oxidation and digestion, a solution prepared with 1.50 g of ammonium persulfate and 4.0 mL of water was added, along with 1.0 mL of nitric acid with a mass fraction of 65%–68%.

3. The method according to claim 2, characterized in that, The first stage of oxidation and digestion includes: heating to 80°C within 5 minutes and holding for 10 minutes, then heating to 120-130°C within 10 minutes and holding for 20 minutes, then cooling to no higher than 35°C and depressurizing; The second stage of oxidation and digestion includes: heating to 100°C within 8 minutes and holding for 5 minutes, then heating to 140-150°C within 10 minutes and holding for 20 minutes, then cooling to no higher than 40°C and depressurizing.

4. The method according to claim 1, characterized in that, The preparation of phase A includes: centrifuging the digestate after the second-stage oxidation and digestion at 6000×g for 10 min, washing the solid phase three times with a washing solution containing 0.20 mol / L HNO3 and 0.10 mol / L (NH4)2SO4, with each washing solution being 5.0 mL, combining the digestate and each washing solution, and making up to 100.0 mL with 0.20 mol / L HNO3 to obtain phase A.

5. The method according to claim 1, characterized in that, The first complex extract contains 0.80 mol / L ammonium acetate and 0.10 mol / L disodium EDTA, does not contain hydroxylamine, and has a pH of 4.8–5.2; The preparation of phase B includes: adding 20.0 mL of the first complexing extract to the solid phase obtained after preparing phase A, extracting at 58–62 °C for 20 min, separating the solid and liquid phases, adding another 10.0 mL of the first complexing extract, extracting at 58–62 °C for 10 min, then washing the residue with 5.0 mL of water at least 3 times, combining the extracts and washes and adjusting the volume to 100.0 mL to obtain phase B.

6. The method according to claim 1, characterized in that, The oxidation micro-melting process includes: washing and drying the residue obtained after preparing the B phase, placing it in a high-purity metallic iron crucible, adding 0.25g of anhydrous Na2CO3 and 0.25g of Na2O2 and mixing them, then covering it with 0.25g of Na2O2; covering the crucible with a lid but not sealing it, heating it to 430-470℃ at 5-10℃ / min and holding it for 3-5min, then heating it to 600-640℃ and holding it for 5-8min.

7. The method according to claim 6, characterized in that, The treatment of the micro-melted product includes: cooling the crucible to no higher than 30°C, adding water in small batches until the cumulative volume reaches 15.0 mL, heating in a non-sealed manner at 60–70°C for 5 min; acidifying the solution to pH 1.0–2.0 with a nitric acid aqueous solution at a volume ratio of 1:1 under external cooling and stirring conditions; adding 0.30 mL of 30% H2O2 after the liquid temperature drops below 40°C, and treating in a non-sealed manner at 70–80°C for 10 min.

8. The method according to claim 7, characterized in that, When insoluble particles still exist in the micro-melted product after water immersion, acidification and H2O2 treatment, the insoluble particles are separated, washed with water and dried, and then micro-melted again using fresh Na2CO3 and Na2O2 in the same ratio as in claim 6. The temperature is first raised to 430-470°C and held for 3-5 minutes, and then raised to 650-680°C and held for 2-5 minutes. Combine the acid leaching solutions obtained from one or two micro-melting processes, add 30.0 mL of a second complexing solution containing 0.50 mol / L ammonium acetate and 0.10 mol / L disodium EDTA, adjust the pH to 4.8–5.2, and treat at 58–62 °C for 15 min. For a single micro-melting, bring the volume to 100.0 mL, and for a second micro-melting, bring the volume to 200.0 mL to obtain phase C.

9. The method according to claim 1, characterized in that, Before ICP-OES determination, phase A was diluted at least 25 times, and phases B and C were diluted at least 30 times, respectively. Further dilution was carried out according to the actual salt load so that the total dissolved solids content of each final injection solution did not exceed 1.5 g / L. Phases A, B and C were calibrated using phase-matrix matching, and Sc or Lu was used as an internal standard verified by spectral interference. Cu, Pb and Zn in each phase were determined separately.

10. The method according to claim 9, characterized in that, The content of Cu, Pb or Zn W X Calculate according to the following formula: M X =Σ[(C X,j -C blank,j )×V j ×D j / 1000]; W X =M X / (1000×m)×100%; Where X represents Cu, Pb, or Zn, j represents A phase, B phase, or C phase, and M... X This represents the total mass of element X in the mineral sample, expressed in mg, C. X,j C represents the concentration of element X in the diluted test solution of phase j. blank,j V represents the blank concentration of the corresponding phase throughout the entire process, in mg / L. j D represents the constant volume of phase j, in mL. j The value of m represents the dilution factor of phase j, and m represents the mass of the mineral sample in grams.